Comprehensive Genetic Analysis of a Hungarian Amyotrophic Lateral Sclerosis Cohort - Tripolszki, Kornélia; Gampawar, Piyush; Schmidt, Helena; Nagy, Zsófia F.; Nagy, Dóra; Klivényi, Péter; Engelhardt, József I.; Széll, Márta (Frontiers in Genetics, 2019)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease characterized by the degeneration of motor neurons. Genetic factors play a key role in ALS and identifying variants that contribute to ALS susceptibility is an important step towards understanding the etiology of the disease. The frequency of mutations in ALS patients has been extensively investigated in populations of different ethnic origin. To further delineate the genetic architecture of the Hungarian ALS patients, we aimed to detect potentially damaging variants in major and minor ALS genes and in genes related to other neurogenetic disorders. A combination of repeat-sizing of C9orf72 and next-generation sequencing (NGS) was used to comprehensively assess genetic variations in 107 Hungarian patients with ALS. Potentially causative variants in major ALS genes were detected in 37.4% of patients. As a result of repeat sizing, pathogenic repeat expansions in the C9orf72 gene were detected in 10 patients (9.3%). According to the NGS results, the most frequently mutated genes were NEK1 (5.6%), NEFH, SQSTM1 (3.7%), KIF5A, SPG11 (2.8%), ALS2, CCNF, FUS, MATR3, TBK1 and UBQLN2 (1.9%). Furthermore, potentially pathogenic variants were found in ERBB4, FIG4, GRN and SIGMAR1 genes in single patients. Additional 31 novel or rare known variants were detected in minor ALS genes, as well as 48 variants in genes previously linked to other neurogenetic disorders. The latter finding supports the hypothesis that common pathways in different neurodegenerative diseases may contribute to the development of ALS. While the disease-causing role of several mutations identified in this study has previously been established, other variants may show reduced penetrance or may be rare benign variants. Our findings highlight the necessity for large-scale multi-center studies on ALS patients to gain a more accurate view of the genetic pattern of ALS.